Personal Outreach in a Virtual World - A. Ben Wagner (Issues in Science and Technology Librarianship)
For all the wonders of social media and other forms of virtual communications, I still find the most successful outreach programs are face to face. The power of personal contact is as old as the human race. In today's world, think of the impact a hand-written letter or a phone call has in the midst of our daily flood of e-mail and cell phone texts. In the same way, I am convinced that face-to-face outreach usually has the same high impact because it is increasingly rare. Is not one of the main objectives of the current interest in embedded librarians direct personal contact with patrons?